MOTIVATIONAL FACTORS IN ENGLISH LANGUAGE LEARNING: A STUDY OF FIRST-YEAR LAW STUDENTS AT TASHKENT STATE UNIVERSITY OF LAW - Umirov, Sarvar (Journal of Higher Education and Academic Advancement, 2025)
Objective: This study investigates the factors influencing motivation among English language learners (ELLs) at Tashkent State University of Law, focusing on first-year students enrolled in the "English for Lawyers" module. The research explores how teaching methodologies, curriculum relevance, and assessment practices impact student engagement and contribute to the development of language skills necessary for academic and professional success. Methods: A mixed-methods approach was adopted, involving surveys completed by 40 students and semi-structured interviews with 10 randomly selected participants. The study assesses how interactive learning environments, real-world legal applications, and alternative assessment models affect students' motivation levels. Quantitative data from surveys is complemented by qualitative insights from interviews, providing a comprehensive understanding of the factors shaping student motivation. Results: Students demonstrated higher levels of engagement and motivation when participating in interactive classroom activities, real-world legal scenarios, and project-based assessments. Traditional memorization-focused assessments were found to negatively impact motivation, while creative, problem-solving tasks enhanced students’ confidence and practical skills. Additionally, external factors such as sleep, social media use, and physical well-being played a significant role in influencing classroom performance and focus. Novelty: This study highlights the importance of contextualized and student-centered teaching approaches in boosting motivation among law students learning English. It emphasizes the value of incorporating practical, career-relevant materials and dynamic assessment models to create a more engaging and effective learning environment. The research contributes to the broader discourse on educational reform in Uzbekistan, advocating for pedagogical strategies that align with students' professional goals and foster long-term academic growth and success.